ChemInform Abstract: Total Synthesis and Assignment of the Absolute Stereochemistry of Xanthoangelol J: Development of a Highly Efficient Method for Claisen—Schmidt Condensation. Issue 28 (15th July 2014) - Kakati, Dwipen; Barua, Nabin C.
Abstract The Claisen—Schmidt condensation of aryl methyl ketones and aromatic aldehydes is optimized with respect to use hydroxylated arenes in both substrates.